Pendampingan Guru Sekolah Dasar dalam Mengembangkan Modul Digital Berbasis Budaya Lokal Angkola Menggunakan Artificial Intelligence - Siti Maryam Pane; Elissa Evawani Tambunan; Lisa Fitri Meidipa (Jurnal Pengabdian kepada Masyarakat Radisi, 2026)
This community service program aimed to enhance elementary school teachers' competencies in developing digital learning modules based on Angkola local culture using Artificial Intelligence (AI). The program was conducted at SD Negeri 200301 Padangsidimpuan from 20–22 May 2026 and involved six teachers. The implementation consisted of needs assessment, training, mentoring, hands-on module development, classroom implementation, and evaluation through pretests, posttests, product validation, and participant satisfaction questionnaires. The program results indicated improved teacher competencies in utilizing AI to develop digital learning materials and greater understanding of integrating Angkola local culture into social studies instruction. All participants successfully produced digital modules containing contextual learning materials, learning activities, assessments, and local cultural values. Product validation demonstrated that the modules met the required standards for content, presentation, language, and media design, making them suitable for classroom implementation. Overall, the program provided practical experience in the responsible use of AI while producing innovative, contextual teaching materials that support the preservation of local culture through education.